2020
DOI: 10.1101/2020.10.28.359109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innervation and Neuronal Control of the Mammalian Sinoatrial Node: A Comprehensive Atlas

Abstract: Cardiac function is under exquisite intrinsic cardiac neural control. Neuroablative techniques to modulate control of cardiac function are currently being studied in patients, albeit with variable and sometimes deleterious results. Recognizing the major gaps in our understanding of cardiac neural control, we sought to evaluate neural regulation of impulse initiation in the sinoatrial node as an initial discovery step. Here, we report an in-depth, multi-scale structural and functional characterization of the in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 79 publications
(112 reference statements)
5
21
0
Order By: Relevance
“…Pacemaker cells, parasympathetic fibers, and sympathetic fibers of the SAN neuronal plexus immunoreactive for HCN4, VChAT, and TH, respectively, were readily identifiable up to 350 µm in depth in the SAN tissue in all whole mount preparations ( n=3 ). Compared with atrial areas adjacent to the root of SVC, the density of nerve fibers within the HCN4-positive meshwork of pacemaker cells was 2–3 fold higher ( n=3 ) consistent with previous publications (18, 19).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Pacemaker cells, parasympathetic fibers, and sympathetic fibers of the SAN neuronal plexus immunoreactive for HCN4, VChAT, and TH, respectively, were readily identifiable up to 350 µm in depth in the SAN tissue in all whole mount preparations ( n=3 ). Compared with atrial areas adjacent to the root of SVC, the density of nerve fibers within the HCN4-positive meshwork of pacemaker cells was 2–3 fold higher ( n=3 ) consistent with previous publications (18, 19).…”
Section: Resultssupporting
confidence: 91%
“…Images of ICG stained for TH, VAChT, and HCN4, confirmed that most neurons in these ganglia were cholinergic (i.e., immunoreactive for VAChT), while others were adrenergic, and that some neurons within ICG were reactive for neither VAChT nor TH ( Fig. 2 ), suggesting the presence of other neurotransmitters within ganglionic neurons (18). We also observed HCN4+ immunoreactivity on the shell of ICG suggesting that some HCN4+ satellite cells may be present around the ganglia.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, the proportion of adrenergic and nitrergic NS is also almost unfluctuating between the different sGPi. Presumably, the neonatal ICNs are not specialized functionally yet as this is predictable in adult animals (Brack, 2015; Hanna et al, 2021). Nevertheless, one shift from uniform distribution of ICNs was noticed in the piglet VLA sGP, in which the abundance of cholinergic NS was comparatively lesser due to an increase of adrenergic and nitrinergic NS in this sGP.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical phenotype of a neuron may be indicative of its function and, therefore, the shift in proportions of particular neuronal phenotypes provides the anatomical basis for adaptability of ICNs as this was clearly demonstrated for the heart rate decreases in respect to age of some animal species following shift in abundance of neurons in the sympathetic chain ganglia (Woods et al, 1977; Yiallourou et al, 2012). Since both, the chemical phenotype and the location of ICNs, may be strongly associated with their function, an analysis of distribution of the phenotypically distinct ICNs should contribute to disclosure of the genuine cause of different structural patterns of GP in diverse animal species (Aksu et al, 2021; Brack, 2015; Hanna et al, 2021). Furthermore, the widespread neural communications with and between ICNs ensure an integration of the extrinsic and intracardiac signals within GP in which the interplay between cholinergic, adrenergic, and other chemical phenotypes of ICNs occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, satellite glial cells are also abundantly present within the intrinsic cardiac nervous system, [ 94 ] and have been demonstrated to become injured upon catheter ablation of atrial fibrillation [ 95 ]. Interestingly, higher serum concentrations of S100B after catheter ablation of atrial fibrillation were associated with a lower recurrence rate [ 95 ].…”
Section: Interventionsmentioning
confidence: 99%